Numerical analysis of different heating systems for warm sheet metal forming. Issue 5 (March 2016) - Martins, J.; Alves, J.; Neto, D.; Oliveira, M.; Menezes, L.
Abstract The main goal of this study is to present an analysis of different heating methods frequently used in laboratory scale and in the industrial practice to heat blanks at warm temperatures. In this context, the blank can be heated inside the forming tools (internal method) or using a heating system (external method). In order to perform this analysis, a finite element model is firstly validated with the simulation of the direct resistance system used in a Gleeble testing machine. The predicted temperature was compared with the temperature distribution recorded experimentally and a good agreement was found. Afterwards, a finite element model is used to predict the temperature distribution in the blank during the heating process, when using different heating methods. The analysis also includes the evaluation of a cooling phase associated to the transport phase for the external heating methods. The results of this analysis show that neglecting the heating phase and a transport phase could lead to inaccuracies in the simulation of the forming phase.